Conflict: causes, effects and management (2011)
The paper attempts to explore the causes of conflicts and the effects that poorly managed conflict could have on the society. It establishes that while conflict is a usual phenomenon in any human environment, violence is destructive and unusual and conflicts should not be allowed to degenerate into violence. Skilfully managed conflicts can propel development in any human environment, but violence can lead to disintegration and destruction. Four methods of handling conflicts are discussed, each method having an implication on the outcome of conflict. Furthermore, the components of the Alternative Dispute Resolution (ADR) are discussed. The advantages of the ADR which accounted for its growing popularity globally over the adversarial court system are emphasized. Finally, the paper examines the role of youths in peace building and advocates for integration of peace education into the curricular of the educational institutions for the benefit of the youth